The role and therapeutic potential of macrophages in the pathogenesis of diabetic cardiomyopathy - Zhang, Shan; Zhu, Xueying; Chen, Yupeng; Wen, Zhige; Shi, Peiyu; Ni, Qing (Frontiers in Immunology, 2024)
This review provides a comprehensive analysis of the critical role played by macrophages and their underlying mechanisms in the progression of diabetic cardiomyopathy (DCM). It begins by discussing the origins and diverse subtypes of macrophages, elucidating their spatial distribution and modes of intercellular communication, thereby emphasizing their significance in the pathogenesis of DCM.The review then delves into the intricate relationship between macrophages and the onset of DCM, particularly focusing on the epigenetic regulatory mechanisms employed by macrophages in the context of DCM condition. Additionally, the review discusses various therapeutic strategies aimed at targeting macrophages to manage DCM. It specifically highlights the potential of natural food components in alleviating diabetic microvascular complications and examines the modulatory effects of existing hypoglycemic drugs on macrophage activity. These findings, summarized in this review, not only provide fresh insights into the role of macrophages in diabetic microvascular complications but also offer valuable guidance for future therapeutic research and interventions in this field.